Investigating the role of pyrophosphate fructose 6-phosphate 1-phosphotransferase in phloem loading - Smith, Marthinus Luther (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Genetics. Plant Biotechnology)) --Stellenbosch University, 2008.